Growth phase matters: Boosting immunity via Lacticasebacillus-derived membrane vesicles and their interactions with TLR2 pathways - Sandanusova, Miriam; Turkova, Kristyna; Pechackova, Eva; Kotoucek, Jan; Roudnicky, Pavel; Sindelar, Martin; Kubala, Lukas; Ambrozova, Gabriela (Journal of extracellular biology, 2024)
Lipid bi-layered particles known as membrane vesicles (MVs), produced by Gram-positive bacteria are a communication tool throughout the entire bacterial growth. However, the MVs characteristics may vary across all stages of maternal culture growth, leading to inconsistencies in MVs research. This, in turn, hinders their employment as nanocarriers, vaccines and other medical applications. In this study, we aimed to comprehensively characterize MVs derived from Lacticaseibacillus rhamnosus CCM7091 isolated at different growth stages: early exponential (6 h, MV6), late exponential (12 h, MV12) and late stationary phase (48 h, MV48). We observed significant differences in protein content between MV6 and MV48 (data are available via ProteomeXchange with identifier PXD041580), likely contributing to their different immunomodulatory capacities. In vitro analysis demonstrated that MV48 uptake rate by epithelial Caco-2 cells is significantly higher and they stimulate an immune response in murine macrophages RAW 264.7 (elevated production of TNFα, IL-6, IL-10, NO). This correlated with increased expression of lipoteichoic acid (LTA) and enhanced TLR2 signalling in MV48, suggesting that LTA contributes to the immunomodulation. In conclusion, we showed that Lacticaseibacillus rhamnosus CCM7091-derived MVs from the late stationary phase boost the immune response the most effectively, which pre-destines them for therapeutical application as nanocarriers.
Keywords: nanocarriers; immunomodulation; lipoteichoic acid; growth curve; membrane vesicles; Lacticaseibacillus rhamnosus; TLR2